Matrix Metalloproteinase-9 Production following Cardiopulmonary Bypass Was Not Associated with Pulmonary Dysfunction after Cardiac Surgery - Tso-Chou Lin; Feng-Yen Lin; Yi-Wen Lin; Che-Hao Hsu; Go-Shine Huang; Zhi-Fu Wu; Yi-Ting Tsai; Chih-Yuan Lin; Chi-Yuan Li; Chien-Sung Tsai (Mediators of Inflammation)
Background. Cardiopulmonary bypass (CPB) causes release of matrix metalloproteinase- (MMP-) 9, contributing to pulmonary infiltration and dysfunction. The aims were to investigate MMP-9 production and associated perioperative variables and oxygenation following CPB. Methods. Thirty patients undergoing elective cardiac surgery were included. Arterial blood was sampled at 6 sequential points (before anesthesia induction, before CPB and at 2, 4, 6, and 24 h after beginning CPB) for plasma MMP-9 concentrations by ELISA. The perioperative laboratory data and variables, including bypass time, PaO2/FiO2, and extubation time, were also recorded. Results. The plasma MMP-9 concentrations significantly elevated at 2–6 h after beginning CPB (P<0.001) and returned to the preanesthesia level at 24 h (P=0.23), with predominant neutrophil counts after surgery (P<0.001). The plasma MMP-9 levels at 4 and 6 h were not correlated with prolonged CPB time and displayed no association with postoperative PaO2/FiO2, regardless of reduced ratio from preoperative 342.9±81.2 to postoperative 207.3±121.3 mmHg (P<0.001). Conclusion. Elective cardiac surgery with CPB induced short-term elevation of plasma MMP-9 concentrations within 24 hours, however, without significant correlation with CPB time and postoperative pulmonary dysfunction, despite predominantly increased neutrophils and reduced oxygenation.